Analysis of protein from nasopharyngeal carcinoma cell line CNE2 irradiated by X-ray using Raman spectroscopy. Issue 1 (2012) - Ou, Lin; Chen, Yang; Huang, Yangwen; Su, Ying; Lin, Duo; Zou, Changyan; Lei, Jinping
Abstract : Our work aims to explore Raman spectroscopy (RS) to study the effects of total protein of nasopharyngeal carcinoma (NPC) cell line CNE2 treated by different doses of X-ray irradiation. The total protein is extracted from the cell line after irradiation with no incubation (0 h) and with incubation for 72 h, respectively. Both paired-samples t test and support vector machine (SVM) are employed for statistical analysis of Raman spectrum. The results show that several Raman bands assigned to total protein can be detected; and the X-ray irradiation have various effects on different components in total protein, especially for the dose higher than 6 Gy, and also associated with the incubation time after irradiation. The differences of content between 0 h groups and 72 h groups appear at bands of C–S stretching, C–H stretching, O=C–O − stretching and L-phenylalanine. It indicated no significant diversification on structures of protein, while the content may be varied during irradiation. Our spectroscopic results reveal that RS analysis of total protein of cell line irradiated by X-ray, in conjunction with mathematical statistical model, can be a potential method to explore the Raman characterization target of cell radiosensitivity, and then for making known the mechanism of radiosensitivity of tumor further.